Students and Educators Attitudes towards the use of M-Learning: Gender and Smartphone ownership Differences - Al-Emran, Mostafa; Alkhoudary, Yahya Ashour; Mezhuyev, Vitaliy; Al-Emran, Mohammed (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobile learning (M-learning) is relatively becoming a hot topic that attracted the interest of many scholars. Although M-learning is spreading rapidly across many countries in the world, studying the students and educators’ attitudes towards its usage is still in short supply. This study is considered one of the few that attempts to examine the students and educators’ attitudes towards the use of M-learning by focusing on gender and smartphone ownership differences. The data were collected through a questionnaire survey from eight different universities in Dubai, United Arab of Emirates. 141 students and 31 academics participated in the study. The results indicated that the male students and academics were more likely to use the M-learning systems than the females. Moreover, the students and academics who own smartphones were more likely to use the M-learning systems than those who do not so.